THE CONCLUSION OF THE BIOGRAPHY FROM ANALYZING CONSIDERED POEMS: PESHMARGA (FATAH GULY AS CASE STUDY): ژينناما بابەتی د چارچوڤێ هوزانێ دا... ژيان و خە باتا پێشمەرگە (فەتــاح گولى) وەك نموونە - Muhammed, Gulistan Badel; Muhammed, Rijeen Younis (Journal of Duhok University, 2018)
The objective biography as a genrs is a kind of biognaphy through which its authore writes the events of another pertsin’s life. Generally, writing biognaphy is a process that consists of collecting, recotding and organizing the necessary information based on some basic roles. This reflects the features of the kind of the genre. The most crucial feature of this genre is that the authar writes a cumulative recard of evergthing a person does experience to attract the neader’s attention taward this person whe faces struggle in all stations of his life which les this peeson to be an important sample who deserves tobe recarded theaugh which thw neader will dake benefit if his experiences basically, objective biagnaophy is a kind of rhetoric, how ever it has not any boundaries for the poet. This will not only be valuable to highlight life events of the elected person in an impressine way but also will highlight psychological and emotional affects of the impressive rale of thw elected character. “Life and Revalition of the Peshmerga Fatah Gului” is a book written the paet “Habib Kelesh” cauld be a good sample of the objective biagnephy. This baak, which consists of a number of paems, is written in a simple and dinectr way through which the anthor cauld be able to femonstrate his emotions taward “Fatah Guli”. Mare ever the auther cauld be able to show a part of Huli’s particular life with reggering to a part of hos palitcal and revolutionany life. In this part the auther refers to Guli who has spent his life to a chiene freedam for his mation and country.